USER NEEDS ANALYSIS IN HOSTCARE APPLICATION DEVELOPMENT AS A REAL-TIME DIGITAL QUEUE SYSTEM IN HEALTHCARE FACILITIES - Faiz Azzikri; Rahma Laila Sabina; Yusyfina Yuniarti; Anadza Wafiqotul Azizah; Muhammad Fadil Rizki; Taufik Rahmat Kurniawan (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
Healthcare services in Indonesia continue to face challenges in patient queue management, including long waiting times, uncertainty in service schedules, and the need for patients to arrive early to secure queue numbers. These issues reduce service efficiency and negatively affect patient satisfaction. This study aims to analyze user requirements as the foundation for developing HostCare, a real-time digital queue management application designed to improve the efficiency of healthcare services. A quantitative descriptive approach was employed using an online questionnaire distributed to 10 respondents who had previously accessed healthcare services. The collected data were analyzed using descriptive statistics to identify user problems and system requirements. The findings reveal that 70% of respondents experienced long queues, while 60% reported arriving earlier than scheduled to obtain queue numbers. All respondents (100%) expressed interest in using a digital healthcare queue management system. The most expected features include online queue registration (90%), estimated service times (50%), and automatic queue notifications (50%). Furthermore, 90% of respondents indicated their willingness to use and recommend the HostCare application if implemented. The results demonstrate that user requirements analysis provides a strong foundation for developing digital healthcare applications that align with user expectations. Therefore, HostCare has the potential to improve queue management efficiency, reduce patient waiting times, and enhance the overall quality of healthcare services